2021
DOI: 10.1038/s41598-020-79355-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of physical activity and fitness on sleep in sedentary middle-aged adults: the FIT-AGEING study

Abstract: The association of physical activity and fitness with sleep still remains unclear since there is a lack of studies in this field of research using objective measurements of these variables. This study aimed to investigate the association of objectively-measured sedentariness, physical activity levels, and physical fitness with sleep quantity and quality in sedentary middle-aged adults. A total of 74 volunteers (52.7% women; aged 53.7 ± 5.1) were recruited for the present study. Cardiorespiratory fitness was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Conversely, inadequate amounts of exercise and insufficient sleep may be harmful [2,28]. The present findings emphasize the need to encourage physical activity among health workers to help prevent and treat sleep disorders [29].…”
Section: Discussionmentioning
confidence: 64%
“…Conversely, inadequate amounts of exercise and insufficient sleep may be harmful [2,28]. The present findings emphasize the need to encourage physical activity among health workers to help prevent and treat sleep disorders [29].…”
Section: Discussionmentioning
confidence: 64%
“…We make three key contributions to the international cross-national time use and gender The findings of our study suggest that policy and cultural contexts can critically shape the opportunities that men and women encounter to engage in different activities with key well-being and health implications. We found some relevant cross-national differences in time use in activities such as sleeping and personal care, which are known to be associated with physical health and mental well-being [22][23][24][25][26][27][28],…”
Section: Discussionmentioning
confidence: 87%
“…Third, unlike previous studies, we not only study paid work, housework, care work and leisure in general, but also focus on other key markers of men's and women's health and well-being over their life course: sleeping, personal care, eating and studying. Previous research has found that lacking enough sleeping time is associated with poorer health outcomes and mental well-being (22)(23)(24)(25)(26). Studies also found that time spent in physical and active leisure helps to prevent pathologies and mental health problems, while more sedentary leisure -particularly high levels of screen-based leisure-has been found to be associated with physical and mental health problems, especially among the younger cohorts (24,27,28).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study with 74 volunteers (52.7% women; aged 53.7 ± 5.1), higher levels of overall physical activity, and muscular strength were related to better subjective sleep quantity and quality. 26 Weight loss has been reported to reduce the progression of SDB, contributing to improved sleep quality. 27 The value of daily exercise and exposure to daylight as reports Neubauer 25 "can help reinforce the circadian cycle" (p. 2555).…”
Section: Introductionmentioning
confidence: 99%